Diel activity patterns and overlap between Eurasian red squirrels and Siberian chipmunks in native and introduced ranges. Issue 1 (2nd January 2021) - Andreoni, Alley; Augugliaro, Claudio; Zozzoli, Rudy; Dartora, Fabio; Mori, Emiliano
Abstract : Differential temporal behaviour promotes the coexistence of similar species, thus reducing interspecific competition. We investigated the overlap of activity patterns of invasive Siberian chipmunks Eutamias sibiricus and native Eurasian red squirrels Sciurus vulgaris in northeastern Italy; then, we compared our data with the activity of the same squirrel species in Mongolia, where both of them are native. Siberian chipmunks and Eurasian red squirrels resulted to be strictly diurnal species throughout their range. Both in the native and in the introduced range, the temporal activity of the Siberian chipmunk moderately overlapped with that of the larger Eurasian red squirrel, thus suggesting a limited temporal partitioning among these rodents. Levels of temporal overlap did not significantly differ between the native and the introduced range of the Siberian chipmunk. Our results provide further evidence that direct competitions may not occur between native Eurasian red squirrels and invasive Siberian chipmunks in Europe. This may be reflected by the different peaks of activity we found in spite of the general overlap in diel activity pattern, and/or by other unmeasured processes such as segregation in a spatial occurrence at the fine scale.